Factors that carry way the appearance of anxiety during the COVID-19 pandemic - Becerril, Carlos E. J.; Barrones, Viviana A.; Hernandez, Luis R. P.; Ramírez, Enya A. O.; Gutierrez, Felix O.; Torres, Jose M. Z. (International Journal Of Community Medicine And Public Health, 2022)
Anxiety is a central phenomenon that is most often characterized by a diffuse, unpleasant and vague feeling of apprehension, often accompanied by vegetative symptoms such as headache, diaphoresis, tachycardia, chest tightness and restlessness; symptoms often vary among individuals. Systematic review of articles was realized. A literature search was conducted through digital platforms. Twenty articles published during the years 2020 and 2021 were analyzed, in English and Spanish, related to anxiety during the COVID-19 pandemic. The increase in anxiety was observed as a result of the different factors that emerged from the COVID-19 pandemic; the effects on mental health, when exceeded, can have serious consequences both at the individual and societal levels. Some indicators are the public health measures, as the main factor is social distancing, misinformation and fear of contagion. However, the factor with the greatest increase in anxiety is credited to the economy, which has been affected in all countries, generating critical situations in companies around the world, unemployment and economic difficulties for most families and individuals. Based on what was observed in this analysis, it was found that there are different types of factors that trigger an increase in anxiety, however, the main factors that had a higher rate of causing anxiety were social isolation and concern about the economy, creating uncertainty about the health emergency being experienced.